Optimalisasi Teknologi Digital Sebagai Sarana Penguatan Citra Diri Dan Kesehatan Mental Pada Generasi Muda Menuju Indonesia Emas 2045 - Haikal Arif P; Devina Putri S; Riski Andika (CV. ITTC INDONESIA, 2025)
In today’s era of globalization, the development of digital technology is rapidly advancing, bringing significant impact on all groups, including the younger generation. With the current advancements in technology, various information can be easily accessed through social media, short video apps, and internet access, which facilitate interaction with others without the need for face-to-face meetings. However, there are challaenges faced, such as sosial media addiction, loss of-image, and the deterioration of mental health among the younger generation. The community service activity at SMAN 6 South Tanggerang aims to educate students on the importance of utilizing existing digital technology to strengthen self-image and mental health in order to realize Indonesia’s vision of becoming a golden nation by 2045.